Does emigration increase the wages of non-emigrants in sending countries - Benjamin Elsner (IZA World of Labor, 2022)
How migration affects labor markets in receiving countries is well understood, but less is known about how migration affects labor markets in sending countries, particularly the wages of workers who do not emigrate. Most studies find that emigration increases wages in the sending country but only for non-emigrants with substitutable skills similar to those of emigrants; non-emigrants with different (complementary) skills lose. These wage reactions are short-term effects, however. If a country loses many highly educated workers, the economy can become less productive altogether, leading to lower wages for everyone in the long term.
Keywords: F22; J61; O15; 330; emigration; wages; human capital